After Ethnos - Rees, Tobias (Duke University Press, 2018)
For most of the twentieth century, anthropologists understood themselves as ethnographers. The art of anthropology was the fieldwork-based description of faraway others-of how social structures secretly organized the living-together of a given society, of how a people had endowed the world surrounding them with cultural meaning. While the poetics and politics of anthropology have changed dramatically over the course of a century, the basic equation of anthropology with ethnography-as well as the definition of the human as a social and cultural being-has remained so evident that the possibility of questioning it occurred to hardly anyone. In After Ethnos Tobias Rees endeavors to decouple anthropology from ethnography-and the human from society and culture-and explores the manifold possibilities of practicing a question-based rather than an answer-based anthropology that emanates from this decoupling. What emerges from Rees's provocations is a new understanding of anthropology as a philosophically and poetically inclined, fieldwork-based investigation of what it could mean to be human when the established concepts of the human on which anthropology has been built increasingly fail us.